The corner the complete miniseries - Butler, Henry 1949-2018; Harris, Corey 1969- (Home Box Office, 2009)
"The Corner" is a 2000 HBO drama television miniseries based on the nonfiction book "The Corner": A Year in the Life of an Inner-City Neighborhood by David Simon and Ed Burns and adapted for television by Simon and David Mills. It premiered on premium cable network HBO in the United States on April 16, 2000 and concluded its six-part run on May 21, 2000. The series was released on DVD on July 22, 2003. It won the Primetime Emmy Award for Outstanding Miniseries in 2000.
Bildformat 1.33:1 full frame
Orig.: USA 2000
Keywords: Burns, Edward -- 1946- -- Television adaptations.; Simon, David -- 1960- -- Television adaptations.; Burns, Edward -- 1946-; Simon, David -- 1960-; Violence -- Drama.; Drugs -- Drama.; African American families -- Maryland -- Baltimore -- Drama.; Inner cities -- Maryland -- Baltimore -- Drama.; Television series; Gewalt; Verfilmung; Familie; Schwarze; Innenstadt; Droge; Baltimore, Md.; Fernsehserie; DVD-Video